Interior dan Branding untuk Memunculkan Identitas Natura - Devita Lesmana; Gervasius Herry Purwoko; Rani Prihatmanti (Universitas Ciputra Surabaya, 2015)
Nowadays, business development is accelerating and advancing rapidly because of the supports from many parties, including the government. This advancement has both positive and negative impacts on our society. In the positive side, many of the younger generations emerged to create job opportunities for those who need them. Consequently, this new jobs help strengthen our nation’s economy. In the other hand, the rising businesses are not always linearly correlated to the increase of the quality of those businesses. The quality of a business is greatly affected by the brand identity and the quality of the interior design of the business itself. Therefore, we proudly present Devita Lee Interior Specialist to be the solution of those problems above.In relation with the excellence of the business offered, Natura Resort & Villa is the perfect study case to apply the mentioned service. From multiple researches and surveys, Natura Resort & Villa emphasized the value of body and soul retreat alongside with their vision, life that enlivens. This discourse becomes the base framework for the interior design applied to the lobby area, the restaurant, and one type of villa. The most prominent design application is from the modern natural design style. The natural style implements materials from nature such as wood, bamboo, and rock with their natural colors as the interior design elements. Moreover, the materials are obtained locally, which truly in accordance with life that enlivens. While the modern style comes from the geometric shapes of the design. The next application is shown from the natural tones: dark brown, light brown, cream, and soft green, as the color accents. The next application is the election of the static or dynamic shapes, which moves uniformly.